A new genus and three new species of whiteflies (Aleyrodidae: Homoptera) from the cardamom ecosystem, South India - DAVID, S SELVAKUMARAN, B VASANTHARAJ (Journal of Spices and Aromatic Crops, 1996)
A new genus and species of whitefly Sphericaleyrodes bambusae from Bambusa sp., and two new species, namely, Aleuromarginatus erythrinae from Erythrina indica and Cohicaleyrodes mappiae from Mappia sp. collected from the cardamom ecosystem in South India are described.